Role of Intermediate dose escalation of radiotherapy in the survival of unresectable stage III non-small cell lung cancer patients in the era of immunotherapy - Amin, Saber A.; Lin, Chi; Ganti, Apar K.; Zhen, Weining Ken; Zhang, Chi (Frontiers in Oncology, 2026)
BackgroundThe role of dose escalation of radiotherapy (RT) in unresectable stage III NSCLC followed by immunotherapy is unclear. The objective of the current study is to investigate if intermediate dose escalation (IDE) is beneficial in stage III NSCLC patients who receive definitive concurrent chemoradiation (dcCRT) followed by immunotherapy.Materials and methodsThe study used data from the National Cancer database. Multivariable Cox regression analysis was used to assess the all-cause mortality of patients who received standard RT dose (SD) (60 Gy ± 10%) and IDE (64–74 Gy).Results47,315 patients were diagnosed in the era before immunotherapy and received dcCRT only, while 4,947 patients were treated with dcCRT and immunotherapy. In the cohort with dcCRT only, patients who received SD had statistically significant worse mortality but clinically minimal difference compared to patients with IDE (HR: 1.09, 95% CI: 1.07-1.12; p<0.0001). In the era of immunotherapy, SD was still associated with worse mortality compared to IDE (HR: 1.17, 95% CI: 1.03-1.33; p=0.02). However, the survival benefit associated with IDE was only restricted to patients who started immunotherapy within six weeks after RT completion (HR: 1.26, 95% CI: 1.05-1.6; p=0.01). There was no difference in mortality between SD and IDE among patients who started immunotherapy between 7–10 weeks (HR: 1.13, 95% CI: 0.88-1.45; p=0.35) or >10 weeks after RT completion (HR: 0.74, 95% CI: 0.51-1.07; p=0.11).ConclusionIDE of RT is not needed for patients diagnosed with stage III unresectable NSCLC who receive immunotherapy > six weeks after dcCRT.